Experimental investigations on process parameters for manufacturing of antenna reflectors using vacuum infusion process. (29th December 2020) - Gajjar, Tushar; Shah, Dhaval B.; Joshi, Shashikant J.; Patel, Kaushik M.
Abstract: Carbon fiber reinforcement polymers (CFRPs) are commonly used in aerospace, automobile, and sports industries due to its superior properties compared to conventional metal and alloys. Vacuum infusion process (VIP) is one of the more versatile open mold composite manufacturing techniques because of its economic viability. This paper describes the fabrication of CFRP antenna reflectors used in space communication applications using VIP. Number of layers and pressure gradient were considered as process parameters to evaluate dimensional accuracy. Non‐contact 3D scanning has been used to measure the deviation from fabricated reflector and theoretical CAD model of reflector. Subsequent spring‐back deformation has also been obtained for each reflector. Part thickness at various locations along the length has been measured, whereas the fiber volume fraction has been calculated for each reflector. ANSYS Fluent software has been utilized to acquire pressure drop throughout the reflector, and the calculated pressure drop was validated by relating compaction pressure and volume fraction. The mold filling time has also been measured during the manufacturing process for different laminate thicknesses. Abstract :